Data processing in luminescence dating analysis: An exemplary workflow using the R package 'Luminescence'. (19th March 2015) - Fuchs, Margret C.; Kreutzer, Sebastian; Burow, Christoph; Dietze, Michael; Fischer, Manfred; Schmidt, Christoph; Fuchs, Markus
Abstract: The first version of theR package 'Luminescence' was released and published in 2012. Since then, the package has been continuously improved by implementing further measurement protocols, adding age models, and extending functions. In geoscientific applications, luminescence dating requires a series of data processing procedures. A comprehensive and replicate analysis of luminescence data using theR package 'Luminescence', therefore, suggests combining selected functions. With this contribution, we provide a practical example of a workﬂow from reading measurement data to age modelling. The exemplary data processing routine is applied to an OSL data set of a ﬂuvial sediment sample from the Pamir Mountains.